"Do Some Wondering": Children and their Self‐Understanding Selves in Early Elementary Classrooms. Issue 2 (24th April 2016) - Aronson, Matt; Bialostok, Steve
Abstract : Self‐knowledge has been a central theme in many diagnoses of late modernity, and it has cued scholars to investigate everyday situations in which people express reflexive selves. Using participant observation and interview data, we examined two American elementary classrooms where children learn to express a type of "self‐understanding self" called the enterprising child. We suggest that this form of self emerges through classroom talk characterized by the popular pedagogical concept of metacognition, which encourages the learner to be aware of her thinking and learning and, crucially, to express an awareness of herself as a thinker and learner. We emphasize an interactionist view toward the situational self, and argue that how teachers manage classroom discourse socializes children into venerating the dispositional tendencies that correspond with new capitalist workplaces. We conclude by discussing the implications this may have for modern personhood, symbolic inequality in classrooms, and the political economy of linguistic forms.